1993
DOI: 10.1121/1.407347
|View full text |Cite
|
Sign up to set email alerts
|

Ear-canal impedance and reflection coefficient in human infants and adults

Abstract: The ear-canal impedance and reflection coefficient were measured in an adult group and in groups of infants of age 1, 3, 6, 12, and 24 months over frequency range 125-10,700 Hz. The development of the external ear canal and middle ear strongly affect input impedance and reflection coefficient responses, and this development is not yet complete at age 24 months. Contributing factors include growth of the area and length of the ear canal, a resonance in the ear-canal walls of younger infants, and a probable infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
443
5
24

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 387 publications
(527 citation statements)
references
References 15 publications
(24 reference statements)
55
443
5
24
Order By: Relevance
“…À6 dB for every ear. The tendency for all the percentiles of L F0 to increase above 6 kHz was due to an increase in jRj at this frequency range, as further discussed below and consistent with previous group measurements of jRj 2 (e.g., Keefe et al, 1993). The phase of the transfer-function H F0 for the percentiles shown in the lower panel of Fig.…”
Section: B Acoustic Transfer-function Measurementssupporting
confidence: 72%
See 2 more Smart Citations
“…À6 dB for every ear. The tendency for all the percentiles of L F0 to increase above 6 kHz was due to an increase in jRj at this frequency range, as further discussed below and consistent with previous group measurements of jRj 2 (e.g., Keefe et al, 1993). The phase of the transfer-function H F0 for the percentiles shown in the lower panel of Fig.…”
Section: B Acoustic Transfer-function Measurementssupporting
confidence: 72%
“…Ear-canal wall losses are important below 1 kHz in young infants (Keefe et al, 1993); they are detectable, but remain small, below 0.4 kHz in adults [Fig. 5(b) in Margolis et al, 1999].…”
Section: Absorbed Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, if there is low-frequency energy trapped in the occluded infant ear (similar to adults), it may be absorbed by the infant's compliant ear canal wall (Keefe et al, 1993(Keefe et al, , 1994, resulting in no net increase in energy passing through to stimulate the cochlea. These preliminary results suggest that there is no effect of occlusion in infants younger than 6 mo of age; however, further studies should be conducted in a larger group of infants to confirm these findings.…”
mentioning
confidence: 99%
“…The agreement between the middle ear input impedance calculated in this study and that of O'Connor and Puria [8] further validates the suggestion that viscous and thermal losses contribute significantly to ear canal acoustics. Further studies that are suggested include quantifying visco-thermal effects in infant ear canals where the walls of the ear canal are more compliant than in adults [4], and the effect of speaker/microphone location in the ear canal on visco-thermal losses [14].…”
Section: Discussionmentioning
confidence: 99%